2021
DOI: 10.1136/bcr-2020-238716
|View full text |Cite
|
Sign up to set email alerts
|

FulminantBacillus cereusfood poisoning with fatal multi-organ failure

Abstract: This case represents a rare fulminant course of fried-rice associated food poisoning in an immunocompetent person due to pre-formed exotoxin produced by Bacillus cereus, with severe manifestations of sepsis, including multi-organ (hepatic, renal, cardiac, respiratory and neurological) failure, shock, metabolic acidosis, rhabdomyolysis and coagulopathy. Despite maximal supportive measures (continuous renal replacement therapy, plasmapheresis, N-acetylcysteine infusion and blood products, and broad-spectrum anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…These antibiotics are widely used clinically due to the high prevalence of β-lactamases found among Bacillus cereus group isolates ( 22 24 ), although specific β-lactams (e.g., carbapenems) are also used in combination for the treatment of clinical cases ( 18 , 25 ). Notably, there are reports of poor patient outcomes due to carbapenem resistance ( 12 , 26 ). Recent studies have shown a high prevalence of resistance against penicillin, early cephalosporins, and 3rd and 4th generation cephalosporins among environmental isolates ( 2 , 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…These antibiotics are widely used clinically due to the high prevalence of β-lactamases found among Bacillus cereus group isolates ( 22 24 ), although specific β-lactams (e.g., carbapenems) are also used in combination for the treatment of clinical cases ( 18 , 25 ). Notably, there are reports of poor patient outcomes due to carbapenem resistance ( 12 , 26 ). Recent studies have shown a high prevalence of resistance against penicillin, early cephalosporins, and 3rd and 4th generation cephalosporins among environmental isolates ( 2 , 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our patient presented with elevated liver enzymes and bilirubin after onset, and abdominal ultrasound and CT revealed diffuse abnormalities in the liver. Emetic toxin of B. cereus can cross the blood-brain barrier to attack the central nervous system in immunocompetent people [20,25], causing subarachnoid hemorrhage, parenchymal hemorrhage, brain abscess, cerebral edema, and disturbance of consciousness [15,17]. Patients with hematological diseases combined with central nervous system involvement have a very poor prognosis for B. cereus infection [26].…”
Section: Discussionmentioning
confidence: 99%
“…These B. cereus group strains differ remarkably in their importance to medicine, public health and food safety (Mandic-Mulec et al, 2015). For example, some isolates of B. cereus and B. cytotoxicus strains cause foodborne illness (Naranjo et al, 2011;Guinebretière et al, 2013;Colaco et al, 2021). B. anthracis may cause different forms of anthrax diseases (cutaneous, gastrointestinal, and inhalational anthrax) to both animals and humans (Okinaka et al, 1999;Marston et al, 2005;Cote et al, 2015).…”
Section: Introductionmentioning
confidence: 99%